2021
DOI: 10.11648/j.ajbls.20210904.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Profiles of <i>Pasteurella multocida</i> in Village Chickens (<i>Gallus gallus domesticus</i>) in Maiduguri, Borno State, Nigeria

Abstract: Pasteurella multocida is a highly contagious bacterial pathogen that causes cholera in chickens and water fowls.From September 2019 to February 2021, 600 samples, consisting of tracheal and cloacal swabs (300 samples each), were obtained from 300 seemingly healthy village chickens from households and live bird markets to evaluate the prevalence of P. multocida, test for its antibiotic susceptibility profile and multiple drug resistance patterns. Trachea and cloacal swabs collected were cultured on sheep blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Several studies have shown that certain genes contribute to infection success [7] and encode the biosynthesis of key structural and metabolic molecules [8][9][10] required for adhesion, iron acquisition, colonization, immune response evasion, and survival in the host. Other researchers have identified important non-genetic factors involved in their pathogenesis; for instance, this microorganism is normally found in the oropharyngeal cavity [11][12][13], and immunological failures attributable to coinfections, environmental changes, or zootechnical stress are observed [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that certain genes contribute to infection success [7] and encode the biosynthesis of key structural and metabolic molecules [8][9][10] required for adhesion, iron acquisition, colonization, immune response evasion, and survival in the host. Other researchers have identified important non-genetic factors involved in their pathogenesis; for instance, this microorganism is normally found in the oropharyngeal cavity [11][12][13], and immunological failures attributable to coinfections, environmental changes, or zootechnical stress are observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, chemotherapeutic control of this pathogen is questionable, as it produces residues in food and is expensive, time-consuming, and sometimes ineffective [15]. Therapeutic failures in P. multocida are largely attributable to the resistance developed by many wild strains toward antibiotics [13,16]. Several control and mitigation measures have been established to deal with this problem, including the use of probiotic microorganisms [17], immune modulation through herbal compounds [18], and vaccination [19].…”
Section: Introductionmentioning
confidence: 99%